A sensitive spectrophotometric method for lead determination by flow injection analysis with on-line preconcentration - Di Nezio, Maria Susana (2004)
A new flow injection (FI) system for the determination of Pb(II) at trace level with a preconcentration step and spectrophotometric detection is proposed. It is based on preconcentration of lead ions on chitosan and dithizone-lead complex formation in aqueous medium (pH 9). The chemicals and FIA variables influencing the performance of the system were optimized and applied to the determination of lead in natural, well, and drinking water samples. It is a simple, highly sensitive, and low cost alternative methodology. The method provided a linear rage between 25 and 250 μg l-1, a detection limit of 5.0 ng ml-1 and a sample throughput of 15 h-1. The obtained results of spiked samples are in good agreement between the proposed method and ICP-AES.